Appendiceal adenocarcinoma is associated with better prognosis than cecal adenocarcinoma: a population-based comparative survival study. Issue 1 (23rd February 2023) - Chen, George; Chen, Kay; Sahyoun, Laura; Zaman, Saif; Protiva, Petr
Abstract : Objective: Although appendiceal cancer remains a rare gastrointestinal malignancy compared with colorectal cancer, incidence rates of appendiceal cancer have increased in the last two decades. Appendiceal and cecal adenocarcinomas have distinct genomic profiles, but chemotherapy protocols for these malignancies are the same and survival outcomes between them have not been compared extensively. To this end, we conducted a comparative survival analysis of appendiceal and cecal adenocarcinomas. Design: Using the Surveillance, Epidemiology and End Results (SEER) database, we identified individuals ≥30 years of age with appendiceal or cecal adenocarcinoma from 1975 to 2016. Demographic, clinical and county-level socioeconomic data were extracted using SEER*Stat software. Survival was compared by Mantel-Haenszel log-rank test, and survival curves were generated using the Kaplan-Meier method. Relative HRs for death in the 5-year period following diagnosis were calculated using multivariable Cox regression analysis, adjusted for all other covariates. The significance level was set at p<0.05 for two-tailed tests. Data were analysed using SAS V.9.4 and R software. Results: We identified 6491 patients with appendiceal adenocarcinoma and 99 387 patients with cecal adenocarcinoma. Multivariable Cox regression analysis demonstrated significantly higher cancer-specific and overall survival in appendiceal adenocarcinoma compared with cecal adenocarcinoma. Male sex, older age, earlier year of diagnosis, black race, single marital status, non-Hispanic ethnicity, and non-mucinous histology were associated with increased mortality rates. In addition, counties with lower percentage of individuals below the poverty line and higher colorectal cancer screening rates had better survival. Conclusion: This is the first study to show greater survival in appendiceal adenocarcinoma compared with cecal adenocarcinoma. We also highlighted novel associations of county-level socioeconomic factors with increased mortality in appendiceal adenocarcinoma. Future efforts to develop targeted molecular therapies and reduce socioeconomic barriers to diagnosis and treatment are warranted to improve survival.